SOCIO-CULTURAL ENVIRONMENT OF THE UNIVERSITY, TRADITIONS OF EDUCATIONAL WORK, AND EXTRA-CURRICULAR ACTIVITIES OF FUTURE ENGINEERS - Raisa M. Petruneva; Valentina D. Vasilyeva; Olga V. Toporkova (Высшее образование в России, 2016)
The article considers VSTU traditions of pedagogical work with future engineers, describes the university experience in organization of extra-curricular activities and the development of social and cultural environment at the university. The authors analyze the goals, structure, pedagogical and financial support for the education management system and the results of its activity.